Analisis Korupsi Dalam Perspektif Ilmu Sosial dan Hadis: Implikasinya Terhadap Pendidikan Agama Islam - Ilham Fadhilah (ASWAJA: Jurnal Pendidikan dan Keislaman, 2023)
This article discusses the phenomenon of corruption from the perspectives of social science and hadith, and explores the solutions offered by Islam in addressing corruption. Through qualitative research methods and approaches such as literature study and content analysis, this article delves into the impact of corruption that undermines societal order from various aspects, including economy, social, political, and legal. The study aims to gain a deep understanding of corruption and to offer effective solutions for its eradication from the perspectives of social science and Islam.